The impact of combination therapy of Croton membranaceus and finasteride on benign prostatic hyperplasia (BHP) histo-morphology - George A. Asare; Bernice Asiedu; Vivash Naidoo; Josephine Ablakwa; Samuel Adjei; Brodrick Amoah; Richard Obeng-Kyeremeh; Lesetja Motadi; Mokbul Hossain; Munmun Parveen; Antora Akter; Mahmudul Alam; et al. (Elsevier, 2024)
Introduction: Benign Prostatic hyperplasia (BPH) is one of the age-related conditions that reduce the quality of life in aging men. Treatment modalities range from surgical, use of allopathic drugs, to phytotherapy. Allopathic drugs such as Finasteride and Tamsulosin are often considered to have adverse side effects such as reduced libido and erectile dysfunction. In some countries finasteride is often recommended for BPH although some prefer the use of Croton membranaceus (CM). However, some indigenes combine the two. The study therefore sought to determine impact of this combination therapy of CM and on BPH histomorphologically. Methods: Thirty-five (35) male Sprague Dawley rats (200-250 g) made up of the following groups were established with 5 rats in each group: Group 1, served as the control group; group 2 (model group); group 3 (0.5 mg/kg.b.wt Finasteride- positive control); group 4 [30 mg/kg b.wt. CM (low dose)]; group 5 [300 mg/kg b.wt. CM (high dose)]; group 6 (30 mg/kg b.wt. CM plus 0.5 mg/kg. b.wt. Finasteride); group 7 (300 mg/kg b.wt. CM plus 0.5 mg/kg b.wt. Finasteride). Groups 2-7 were castrated, allowed to rest for 7 days and BPH-induced by administering 5 mg/kg.b.wt testosterone propionate subcutaneously daily for 28 days. CM and Finasteride were administered for 28 days by oral gavage. The prostate and its accessory organs were weighed and examined histologically. Results: In the untreated group (model group) fibromuscular stroma showed the typical characteristic of high epithelial folds with apparent typical hyperplasia. The Finasteride group showed increased rate of apoptosis and progressive decrease in epithelial cell size. At the lower dose of CM, not enough apoptotic areas were observed. However, multiple layers of acinar epithelia were noticed. At the higher dose of CM, few apoptotic cells were seen with acini fluid reduction. The combination of Low dose CM and Finasteride led to fluid level reduction in the acini accompanied by fat droplets and reactive cells infiltration. At a higher dose of CM, papillary fronds were not protruded into the acini. However, acini fluid appeared coagulated. The combination treatment did not have any adverse hepatorenal effect, nor did it change PSA significantly. Conclusion: No overt advantage was seen in this combination therapy, although higher doses of CM in tandem with finasteride may not be advisable. However, there was good tolerability.